Densities, viscosities and specific heat capacities of deep eutectic solvents composed of ethanediol + betaine and ethanediol + L-carnitine for absorbing SO2. (April 2023) - Hou, Yucui; Zhang, Baizhang; Gao, Minjie; Ren, Shuhang; Wu, Weize
Highlights: Deep eutectic solvents (DESs) of ethanediol + betaine/L-carnitine are environmentally benign. Densities, viscosities and specific heat capacities of the DESs for absorbing SO2 were measured. Increasing temperature, SO2 or ethanediol contents enhances the densities and viscosities of DESs. an increase in temperature or ethanediol content increases the specific heat capacities of DESs. Abstract: Two types of deep eutectic solvents (DESs) based on ethanediol and betaine /L-carnitine at different molar ratios from 3:1 to 5:1 are functional for absorbing low-concentration SO2 . Their densities, viscosities and specific heat capacities, which are important for their application in SO2 absorption, have been measured at temperatures from 293.2 K to 333.2 K and SO2 contents from 0 to 0.1501 g SO2 /g DES. The results indicate that an increase in temperature can decrease the densities and viscosities of the DESs, but increase the specific heat capacities of the DESs. An increase in the content of SO2 absorbed in the DESs can increase the densities and viscosities of the DESs. The increase of ethanediol content in the DESs can decrease the densities and viscosities of the DESs, but increase the specific heat capacities of the DESs. The densities of the DESs were correlated using first-order empirical equations as a function of temperature and SO2 content, and the average absolute relative deviations (AARDs) of the density data from the correlations were not more than 0.08 %. The viscosities of the DESs as a function of temperature were correlated using a VFT equation, and the AARDs of the viscosity data from the correlations were not more than 0.8 %. The specific heat capacities of the DESs as a function of temperature were correlated well using a second-order empirical equation, and the AARDs of the specific heat capacities data from the correlations were not more than 0.22 %.